Salivary cortisol in adrenal insufficiency in patients with chronic hepatitis C infection - Ali S Bakry; Eglal M Kenawy; Mona M Abdelmegui; Fatma K Hammad (Wolters Kluwer Medknow Publications, 2020)
Background The assessment of adrenal insufficiency (AI) in cirrhotic patients varies according to the stage of the liver disease. The authors aimed to study the diagnostic role of salivary cortisol (SC) level in the assessment of AI in chronic hepatitis C cirrhotic patients. Patients and methods A case-controlled study of 50 patients with liver cirrhosis owing to chronic hepatitis C infection and 34 apparently healthy persons was conducted. Fasting serum total cortisol (STC), SC, and corticosteroid-binding globulin (CBG) level assessments, as well as calculation of free cortisol level (CFC) were done. Results SC (P<0.000), STC (P<0.000), CBG (P<0.000), and CFC (P<0.000) were reduced significantly in patients compared with controls. A total of 11 (22%) patients were diagnosed with AI by reduced STC level, but only five (10%) were diagnosed by reduced SC. In cirrhotic patients, SC (P<0.000), CFC (P<0.000), and CBG (P<0.000) were significantly decreased with the severity of liver cirrhosis according to Child-Pugh classification. High-density lipoprotein level was positively correlated with SC (P<0.000), CFC (P<0.000), and STC (P<0.000) levels. SC was better correlated with CFC than STC, with a significant difference between the two correlations (z score=−2.716 and P<0.003). On receiver operating characteristic curve analysis, SC (at a cutoff value 5.65 ng/dl) had a sensitivity of 76% and specificity of 87.5% compared with 38 and 97.3%, respectively, for STC (at a cutoff value of 12.6 μg/dl). Conclusion SC correlated well with CFC and is more sensitive than serum total cortisol in the diagnosis of AI in cirrhotic patients.